HEMERA Couples the Proteolysis and Transcriptional Activity of PHYTOCHROME INTERACTING FACTORs in Arabidopsis Photomorphogenesis. Issue 5 (5th May 2015) - Qiu, Yongjian; Li, Meina; Pasoreck, Elise K.; Long, Lingyun; Shi, Yiting; Galvão, Rafaelo M.; Chou, Conrad L.; Wang, He; Sun, Amanda Y.; Zhang, Yiyin C.; Jiang, Anna; Chen, Meng
Abstract : HEMERA couples the degradation and transcriptional activity of PIFs to tightly control hypocotyl growth during Arabidopsis photomorphogenesis. Abstract: Phytochromes (phys) are red and far-red photoreceptors that control plant development and growth by promoting the proteolysis of a family of antagonistically acting basic helix-loop-helix transcription factors, the PHYTOCHROME-INTERACTING FACTORs (PIFs). We have previously shown that the degradation of PIF1 and PIF3 requires HEMERA (HMR). However, the biochemical function of HMR and the mechanism by which it mediates PIF degradation remain unclear. Here, we provide genetic evidence that HMR acts upstream of PIFs in regulating hypocotyl growth. Surprisingly, genome-wide analysis of HMR- and PIF-dependent genes reveals that HMR is also required for the transactivation of a subset of PIF direct-target genes. We show that HMR interacts with all PIFs. The HMR-PIF interaction is mediated mainly by HMR's N-terminal half and PIFs' conserved active-phytochrome B binding motif. In addition, HMR possesses an acidic nine-amino-acid transcriptional activation domain (9aaTAD ) and a loss-of-function mutation in this 9aaTAD impairs the expression of PIF target genes and the destruction of PIF1 and PIF3. Together, these in vivo results support a regulatory mechanism for PIFs in which HMR is a transcriptional coactivator binding directly to PIFs and the 9aaTAD of HMR couples the degradation of PIF1 and PIF3 with the transactivation of PIF target genes.